A new approach for modelling insolation from the space perspective - Prakhova, S.; Suleimanov, I.; Rehbock, Volker (HIKARI Ltd, 2014)
In the current project we have developed a novel insolation model which allows users to incorporate the impact of space activity (solar flares, galactic radiation) on the Earth’s climate. The incoming radiation was modelled as a flux passing through a cross-section (latitudinal belt), and the changes of light throughout the year were represented by an ellipse with changing parameters. This approach has allowed us to get the results for any latitude at any particular time. Obtained results indicate an average accuracy of 97% with only a few percent less for polar regions.